PENERAPAN PENDEKATAN SUPERVISI KOLABORATIF UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SDN (INTI) SUNGAI MIAI 11 - Rahmaniah; Arief Prasetya, Muhammad; Metroyadi; Sakka, Ambo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Collaborative supervision is an approach to educational supervision that emphasizes equal cooperation between supervisors (e.g., principals or supervisors) and teachers to improve the quality of learning. This study employed a qualitative approach with a descriptive research type. The subjects were principal and teachers at SDN (Inti) Sungai Miai 11 who served as research informants. Data collection techniques were conducted through in-depth interviews with informants to obtain comprehensive information regarding the experiences, perceptions, and practices of collaborative supervision implemented. During the interview process, the researcher also systematically recorded all information obtained to ensure data accuracy and completeness. The collected data were analyzed using qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the collaborative supervision approach has a positive contribution to improving teachers' professional competence. This is reflected in the increased ability of teachers to plan more structured learning, implement more interactive and student-centered learning, and conduct more effective learning evaluations. In addition, this approach also encourages more open communication between teachers and supervisors, increases reflective awareness, and builds a conducive collaborative culture in the school environment. Therefore, the implementation of collaborative supervision on an ongoing basis needs to be developed as part of efforts to improve the quality of education in elementary schools.